1989
DOI: 10.1346/ccmn.1989.0370505
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Origin of Analcime in Marginal Lacustrine Mudstones of the Green River Formation, South-Central Uinta Basin, Utah

Abstract: X-Ray powder diffraction and thin section analyses indicate that marginal lacustrine mudstones of the Green River Formation in the south-central Uinta basin, Utah, contain abundant analcime. The analcime has a low Si/A1 ratio (<2.31) and occurs as very fine grained disseminated crystals and, to a lesser extent, as coarser-grained pore-filling cement. Analcime-rich mudstones and associated sandstones, siltstones, and carbonates lack volcanic detritus and zeolites other than analcime, thus making it diflicult to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 37 publications
(45 reference statements)
3
22
0
Order By: Relevance
“…The sizable decrease of quartz contents in the upper URU is possibly related to reduced chemical weathering (see also Williams et al, 2012), as this mineral is more resistant than feldspars and rock fragments (Coney et al, 2007). In turn, analcime occurs both as a primary mineral in alkaline igneous rocks but can also be authigenically formed (Remy and Ferrell, 1989;Schneider et al, 2006). The latter is the most possible origin of this mineral in Coll de Terrers, as no signals of igneous rocks have been found in the succession.…”
Section: Mineralogy and Elemental Successionmentioning
confidence: 99%
“…The sizable decrease of quartz contents in the upper URU is possibly related to reduced chemical weathering (see also Williams et al, 2012), as this mineral is more resistant than feldspars and rock fragments (Coney et al, 2007). In turn, analcime occurs both as a primary mineral in alkaline igneous rocks but can also be authigenically formed (Remy and Ferrell, 1989;Schneider et al, 2006). The latter is the most possible origin of this mineral in Coll de Terrers, as no signals of igneous rocks have been found in the succession.…”
Section: Mineralogy and Elemental Successionmentioning
confidence: 99%
“…While volcanic glass is the most frequent precursor of zeolites in saline-alkaline lakes (Surdam and Sheppard, 1978;Boles and Surdam, 1979), these minerals can also form at the expense of other materials, such as clay minerals, feldspars, and feldspathoids (Hay and Sheppard, 2001). Analcime in particular has been recorded in several cases in lacustrine sediments free of associated volcaniclastic material (Hay, 1966;Gall and Hyde, 1989;Remy and Ferrell, 1989;Renaut, 1993;English, 2001).…”
Section: Analcime Authigenesismentioning
confidence: 99%
“…Iijima and Hay (1968) reported that the Si/Al ratio of the analcime ranged from 1.95 to 2.81 and suggested that this variation might be caused by the reaction of analcime to authigenic feldspar, and may also indicate that analcime associated with authigenic feldspar has a lower Si/Al ratio than in analcime without feldspar with a Si/Al ratio in excess of 2.30. Researchers have suggested that analcime may form as an alteration product of clays deposited in saline and highly alkaline lakes (Hay and Moiola, 1963;Hay, 1970;Ataman and Gü ndog du, 1982;Hay and Guldman, 1986;Remy and Ferrell, 1989;English, 2001;Sheppard and Hay, 2001). Detrital clay minerals are known to react extensively in a saline, alkaline environment (Hay and Moiola, 1963;Hay, 1966;Brobst and Tucker, 1973;Hay and Guldman, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…composition of the volcanic material, water temperature (30À45ºC), and pH (between 8 and 9) (Hay, 1966;Sheppard and Gude, 1969;Ataman and Beseme, 1972;Surdam and Parker, 1972;Gü ndog du et al, 1996, Temel and. In several cases analcime has been identified in lacustrine sediments free of associated volcaniclastic material (Hay, 1966;Sheppard and Gude, 1969;Gall and Hyde, 1989;Remy and Ferrell, 1989;Renaut, 1993;English, 2001; Karakas°a nd Kadir, 2006;Kadir et al, 2008). The physicochemical conditions necessary to form analcime from non-volcanic materials in lacustrine sediments have been studied (Ataman and Gü ndog du, 1982;English, 2001;Campo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%